Digital Transformation Readiness Model in Government - Marwan Wahyudin; Rias Kumalasari Devi; Dana Indra Sensuse (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Along with the rapid development of information technology, Digital Transformation (DT) has become a part of everyday life. The COVID-19 pandemic has triggered the occurrence of DT at every level of society in the daily use of technology. However, the implementation of DT is very slow and inefficient and even becomes a problem for employees and the organization. DT implementation in the public sector is expected to be the key to the Government's success. However, many governments fail to implement DT because it only focuses on modernizing technology, not as a whole. Therefore, it is necessary to conduct a study to analyze the marwanfactors of Digital Transformation (DT) Readiness in Government. This research is a qualitative research method with thematic analysis and Fuzzy Delphi method by conducting a Systematic Literature Review (SLR) first for literature study. Based on the results of the SLR, found five dimensions and 19 factors that affect DT Readiness in Government. The five dimensions are People, Process, Technology, Organization, Environment. Based on the thematic analysis results, three additional factors were found in the people dimension: mindset, and organizational factors, namely risk management and knowledge management. This study also provides a model proposal based on the analysis results presented in a conceptual model with 21 analyzed factors. The research can provide understanding factors that affect the readiness of DT in the Government and as the basis for decision-making by stakeholders in the Government.